2021
DOI: 10.1111/cas.15091
|View full text |Cite
|
Sign up to set email alerts
|

Current progress and future perspectives of research on intravascular large B‐cell lymphoma

Abstract: Intravascular large B-cell lymphoma (IVLBCL) is a rare type of extranodal large B-cell lymphoma characterized by the selective growth of tumor cells in the lumina of systemic organ small vessels (Figure 1). 1 The disease mainly affects middle-aged and elderly adults, similar to other types of malignant lymphoma. A peculiar characteristic of the disease is the lack of lymphadenopathy, which is a general characteristic of malignant lymphoma, and the disease develops with nonspecific symptoms such as fever, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…3,29,31 Shimada and Kiyoi recommend work-up by both RSB and BMB if IVBCL is suspected. 38 Another diagnosis may also be responsible for the patient's presentation. Review of studies where RSB did not yield a diagnosis of IVBCL revealed numerous other neoplastic, auto-immune, and infectious etiologies of a patient's symptomatology including various other types of lymphoma, acute disseminated encephalomyelitis, Schnitzler syndrome, adult-onset Still's disease, neuro-Behcet disease, sarcoidosis, graft-versus-host disease, POEMS syndrome, systemic lupus erythematosus, polyarteritis nodosa, bacterial infection and tuberculosis.…”
Section: Finishing the Consultmentioning
confidence: 99%
“…3,29,31 Shimada and Kiyoi recommend work-up by both RSB and BMB if IVBCL is suspected. 38 Another diagnosis may also be responsible for the patient's presentation. Review of studies where RSB did not yield a diagnosis of IVBCL revealed numerous other neoplastic, auto-immune, and infectious etiologies of a patient's symptomatology including various other types of lymphoma, acute disseminated encephalomyelitis, Schnitzler syndrome, adult-onset Still's disease, neuro-Behcet disease, sarcoidosis, graft-versus-host disease, POEMS syndrome, systemic lupus erythematosus, polyarteritis nodosa, bacterial infection and tuberculosis.…”
Section: Finishing the Consultmentioning
confidence: 99%
“…IVL does not typically cause lymphadenopathy, unlike diffuse large B-cell lymphoma (DLBCL) with which it shares molecular and genetic signatures. 3 IVL can rarely cause strokes: 4 In an analysis of all published cases from 1957 to 2012 of 654 patients, 5 around half presented with neurological symptoms. Within this group, cognitive impairment/dementia was the most common CNS symptom.…”
Section: Discussionmentioning
confidence: 99%
“…9 Prior to the introduction of rituximab, the median overall survival of patients with IVL with anthracycline-based therapies was 3 years. 3 Japanese and European retrospective studies indicate that progression-free survival was significantly improved with rituximab. 3 PRIMEUR-IVL, a phase II trial involving 38 patients, demonstrated safety of rituximab with CHOP, high-dose methotrexate, and intrathecal chemotherapy for intravascular lymphoma without CNS involvement, with a progression-free survival of 76% over 2 years (95% CI 58-87%).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal treatment for CNS-IVL is not established. 7 , 15 , 16 Most patients with IVL with or without CNS involvement are treated with anthracycline-based chemoimmunotherapy (CIT), frequently rituximab, cyclophosphamide, hydroxydoxorubicin, vincristine and prednisone (RCHOP), and without any CNS-directed therapy. 15 , 17 , 18 In the European patients with IVL with both CNS and non-CNS involvements, RCHOP has resulted in 88% complete remission rate (CRR), 91% overall response rate (ORR) and a 3-year overall survival (OS) in 81% of patients.…”
Section: Introductionmentioning
confidence: 99%
“… 15 However, the experience with CNS-directed therapy in management of IVL patients is limited and further investigation and clinical experience are required. 16 …”
Section: Introductionmentioning
confidence: 99%